Responses to Exacerbated Individualism and Postmodern Thinking, on the Subject of Human Rights - Bustamante Alarcón, Reynaldo (2009)
This essay addresses two aspects of the reflections on human rights. First, the author develops an analysis of the individualism that exacerbates individuality to the point of disregarding the community and denying the responsibility of the individual in the development of others. In the second place, the questions that seek the abandonment of the cultural project that gave rise to rights: the Enlightenment and modern project. In each case, the ideas expressed imply a particular anthropological approach, as well as a position on the philosophy underlying human rights.